The Correlation between The Level of Knowledge of Female Adolescent about Personal Hygiene and the Incidences of Vaginal Discharge in Grade XI Female Students of Senior High School 1 Rogojampi Banyuwangi - Kristiana, Dita (Sahabat Publikasi Kuu, 2025)
Introduction: There is a composite index about knowledge of Adolescent Reproductive Health, and the result is 52.4%. Symptoms of vaginal discharge are also experienced by unmarried women or female adolescent aged 15-24 years, which is around 31.8%. The inhibiting factors for healthy behavior in efforts to prevent and treat vaginal discharge include lack of knowledge and awareness of individuals or adolescents about hygienitas.Purpose: The study aimed to determine the relationship between the level of knowledge of female adolescent about personal hygiene with the incidence of vaginal discharge in students of Grade XI at 1 Rogojampi Senior High School.Design/methods/approach: The study implied quantitative research with Observational research design with a cross sectional study approach to administering questionnaires. The population in this study were female adolescent aged 15-18 years in grade XI at 1 Rogojampi Senior High School with 67 female respondents. The study applied purposive sampling technique. Findings/results: Based on statistical tests, the p-value is 0.047 <0.05, which means that there is a correlation between the level of knowledge of female adolescent about personal hygiene and the incidence of vaginal discharge in grade XI at 1 Rogojampi Senior High School.Conclusions: There is a correlation between the level of knowledge of female adolescent about personal hygiene and the incidence of vaginal discharge